Factibilidad para la producción y comercialización de mantequilla de maní en el cantón Paltas, Provincia de Loja - Carche Riofrio, Edwin Aurelio (2023)
This study aims to determine whether peanut butter can be produced and commercialized in the canton of Paltas, province of Loja. To fulfill the objectives, methods such as inductive, deductive, descriptive and analytical were used. In addition, research techniques such as the survey applied to the families of the canton of Paltas, and thus determine the tastes and preferences of consumers. Subsequently we proceeded to analyze the different studies of the project: regarding the market study it was determined that there is an unsatisfied demand of 47,426.31 pounds of peanut butter; as for the technical study, the company according to its size will offer 46,980 pounds of peanut butter which is equivalent to 99% of the unsatisfied demand; regarding the economic and financial study, the company to start its activities requires an investment of 22,589.93 U.S. dollars, which is equivalent to 99% of the unsatisfied demand; regarding the economic and financial study, the company to start its activities requires an investment of 22,589.93 U.S. dollars, which is equivalent to 99% of the unsatisfied demand. A total of 589.93 US dollars will be financed by 78% of the partners' contributions and 22% through a Ban Ecuador credit; based on the financial evaluation, the project appears feasible based on the net present value of 20,524.62 US dollars, or 46 percent internal rate of return. An investment of 85% is recovered in one year, ten months, 28 days; the company receives 0.21 US cents for every dollar invested; the project's sensitivity analysis indicates an increase of 8.80% in costs and a decrease of 7.95% in income.